2018
DOI: 10.1111/php.12888
|View full text |Cite
|
Sign up to set email alerts
|

Development of Cotton Fabrics with Durable UV Protective and Self‐cleaning Property by Deposition of Low TiO2 Levels through Sol–gel Process

Abstract: In this article, the deposition of TiO on cotton fabric using sol-gel technique has been described. Various process routes (pad-dry-cure, pad-dry-hydrothermal and pad-dry-solvothermal) were examined to impart a stable coating of TiO on fabric. The role of precursor concentration, process temperature and time of treatment were studied to aim at a wash durable, UV protective and self-cleaning property in the treated fabric. EDX and ICP-MS techniques were used to examine the add-on percentage of TiO on cotton fab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…These three diffraction peaks represent the anatase phase of TiO 2 present on the fabric surface. 25 The presence of characteristic peaks corresponding to the cellulose crystalline in the XRD pattern of TiO 2 coated fabrics indicates that the coating of TiO 2 on the cotton fabric surface does not affect the inherent crystalline structure of the cotton. Moreover, it was also observed from the XRD studies that anatase phase of TiO 2 is retained aer mixing with RB-21 as shown in the XRD pattern of RB-21/TiO 2 coated cotton fabrics.…”
Section: X-ray Diffraction Studiesmentioning
confidence: 96%
“…These three diffraction peaks represent the anatase phase of TiO 2 present on the fabric surface. 25 The presence of characteristic peaks corresponding to the cellulose crystalline in the XRD pattern of TiO 2 coated fabrics indicates that the coating of TiO 2 on the cotton fabric surface does not affect the inherent crystalline structure of the cotton. Moreover, it was also observed from the XRD studies that anatase phase of TiO 2 is retained aer mixing with RB-21 as shown in the XRD pattern of RB-21/TiO 2 coated cotton fabrics.…”
Section: X-ray Diffraction Studiesmentioning
confidence: 96%
“…Because of its high absorption capability in the UV region, graphene represents one of the novel materials for the UV protection of textiles that does not lead to harmful photocatalytic degradation [35]. Inorganic UV blockers can be applied in diff erent textile production stages, among which the electrospinning of nanofi bres and fi nishing of fabrics by the sol-gel technique are of great technological importance [44,45]. When applying inorganic UV blockers to textile substrates, researchers have faced several problems associated with the agglomeration of NPs, low adsorption ability of textile fi bres for NPs and low durability of the coating.…”
Section: Inorganic Uv Blockersmentioning
confidence: 99%
“…When applying inorganic UV blockers to textile substrates, researchers have faced several problems associated with the agglomeration of NPs, low adsorption ability of textile fi bres for NPs and low durability of the coating. To resolve these problems, new routes of synthesis of NPs have been introduced to improve the dispersity of NPs, such as the in situ growth of NPs on textile fi bres in the presence of stabilising agents [31, [46][47][48]; and the use of hydrothermal, solvothermal, microwave and sputtering deposition methods [32,45,[49][50][51][52][53][54]. To enhance the adsorption ability of textile fi bres and consequently the washing durability of the coatings, plasma treatments have been used to increase the textile wettability and the surface roughness [54][55][56], polyester fi -bres have been pre-treated with sodium hydroxide to improve their wettability [57,58] and cellulose fi bres have been pre-modifi ed with chloroacetic acid to create new active carboxylic groups [31].…”
Section: Inorganic Uv Blockersmentioning
confidence: 99%
“…Wash durability is also one of the major concern upon which very few researchers have paid serious attention. Several studies have reported that TiO2 coating on textiles could be performed using different pretreatments and techniques [9][10][11].…”
Section: Introductionmentioning
confidence: 99%